Implications of Inclusive Education Policy in Guaranteeing the Rights of Children with Special Needs - Willya Achmad (AL-ISHLAH: Jurnal Pendidikan, 2023)
The goal of this research is to look into the effects of inclusive education policy in Indonesia in order to protect the rights of children with special needs. A systematic literature review was conducted to synthesize the kinds of literature pertaining to inclusive education policy on children with special needs. The kinds of literature were attained from several article search engines, namely Google Scholar and ScienceDirect, published from 2011 to 2023. The data collected includes the rules and regulations, policies, guidelines, and instructions linked with inclusive education. The study's findings reveal that inclusive education policies substantially impact the issue of ensuring that children with special needs are given their rights. Specialized educational services will be provided to children with special needs, and efforts will be made to strengthen the overall inclusive education system and make education more accessible to all children. Improving the quality of human resources, guaranteeing that all students have equal access to special education services, and raising public awareness about the significance of inclusive education are all crucial if we want to see an increase in the effectiveness of inclusive education policies. Therefore, it is desired that all children, including those with special needs, would have equal and adequate educational opportunities.